Class II Correction with Microimplant Supported Molar Distalization: A Report of Two Cases - Zouhair Skaf; Fidèle Nabbout (Hindawi Limited, 2022)
Introduction. Orthodontic treatment of class II malocclusion with conventional treatment modalities can be challenging for the clinician. The use of microimplants to obtain absolute anchorage has become very popular in recent years especially in noncompliant patients. Microimplants are convenient, save time, and produce good treatment results with no need for patient cooperation. A special approach for class II correction with microimplant supported molar distalization has been developed by the authors and is illustrated through two clinical cases. Description. For each clinical case, 0.022" preadjusted brackets were bonded on both arches except on the maxillary first and second premolars with bands on the first and second molars. After leveling and alignment, a 0.017"×0.025" stainless steel wire was fitted on the upper arch, and two microimplants were placed bilaterally between the maxillary second premolar and the first molar. Open coil springs were inserted in the upper archwire on both sides and compressed via a steel ligature on sliding hooks to the microimplants pushing distally simultaneously the first and second maxillary molars. En-masse retraction of the maxillary anterior teeth was then carried out on a 0.019"×0.025" stainless steel closing loop archwire while the posterior segment was anchored to the microimplant with a steel ligature to the first premolar. Results. Class I canine and molar relationship were achieved, and an ideal occlusion was established. Both ANB and FMA angles decreased by 1° due to the counterclockwise rotation effect of the maxillomandibular complex. Skeletal and dental results remained stable three years later. Conclusion. Maxillary molar distalization using coils and buccal microimplants can be regarded as an effective technique in a relatively short time and might be considered a breakthrough in the treatment of class II malocclusions. Microimplants enable the clinician to perform a nonextraction treatment in noncompliant patients who would alternatively be treated only with extractions.